Correction: A dynamic anode boosting sulfamerazine mineralization via electrochemical oxidation. Issue 4 (13th January 2022) - Deng, Fengxia; Xie, Jinyu; Garcia-Rodriguez, Orlando; Jing, Baojian; Zhu, Yingshi; Chen, Zhonglin; Hsu, Jyh-Ping; Jiang, Jizhou; Bai, Shunwen; Qiu, Shan
Abstract : Correction for 'A dynamic anode boosting sulfamerazine mineralization via electrochemical oxidation' by Fengxia Deng et al., J. Mater. Chem. A, 2022, 10, 192–208, DOI: ; 10.1039/D1TA08095D .